Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, Hannah; Hennessy, Sara; Pimmer, Christoph (Research Papers in Education, 2022)
This study reports on the adaptation and outcomes of a teacher professional development (TPD) programme in a rural Zimbabwean secondary school. The programme incorporated Open Educational Resources (OER), specifically OER4school materials, that were provided via tablet computers for teachers and students. A mixed-methods case study was employed to explore teachers’ perceptions, knowledge, experiences of interactive learning and teaching in relation to this TPD, as well as their perceptions and experiences of the role and value of using technology to support student learning. Video data from structured lesson observations were triangulated with teacher post-lesson interviews and thematically coded. The interviews indicated that all teachers demonstrated a change in mindset and a clear understanding of interactive teaching methods. However, the structured observations revealed that only half of the teachers were using these interactive methods. Teachers also emphasised the value of OER and tablet technologies in improving lesson planning and making classroom learning more authentic. The use of technology, as both a TPD medium and as a classroom tool, showed potential to enhance the quality of TPD and teacher quality. Yet more specific teacher development to support the interactive use of technology within the classroom would be beneficial.
Keywords: Author:OpenDevEd; Open education resources; Zimbabwe; educational technology; tablets; teacher education; teacher professional development